Troponin I, laboratory issues, and clinical outcomes in a district general hospital: crossover study with "traditional" markers of myocardial infarction in a total of 1990 patients. Issue 10 (27th September 2004) - Jishi, F; Hudson, P R; Williams, C P; Jones, R P; Davies, G K; Yousef, Z R; Trent, R J; Cowell, R P W
Abstract : Aims: Review of the clinical outcomes and practical issues of replacing traditional cardiac enzymes with troponin I (cTnI) in a district general hospital. Methods: Crossover study of three sequential three month stages during which serial cardiac enzymes were replaced with a single cTnI measurement available at three set times within 24 hours for the duration of the second three month stage. The study was carried out in a 630 bed district general hospital with 1990 admissions of suspected cardiac ischaemia over the study period as a whole. Account was taken of seasonal factors. Results: The introduction of troponin was associated with 8.5% more patients with non-ischaemic heart disease (IHD) being discharged on the day after admission, saving approximately 107 bed days each year. Approximately 50% more patients were diagnosed with myocardial infarction during the cTnI stage. There was no increase in readmission within one month or early death with cTnI. Approximately 3% false positive and 1.5% false negative cTnI results were recorded. All false positive cTnI results were coding errors or attributable to known assay interference effects. All false negatives were potentially explained by sample timing factors. The lack of standardisation in troponin assay services impacts clinically. Conclusion: Younger patients without IHD were discharged earlier during the cTnI stage in apparent safety. Blood sample timing needs to be verified when cTnI is used as an adjunct to early discharge. There were no unexplained false positives or negatives. Standardisation related issues arose.